10-Valent pneumococcal non-typeable H. influenzae protein D conjugate vaccine (PHiD-CV10) versus 13-valent pneumococcal conjugate vaccine (PCV13) as a booster dose to broaden and strengthen protection from otitis media (PREVIX_BOOST) in Australian Aboriginal children: study protocol for a randomised controlled trial. Issue 5 (24th May 2020) - Oguoma, Victor M; Wilson, Nicole; Mulholland, Kim; Santosham, Mathuram; Torzillo, Paul; McIntyre, Peter; Smith-Vaughan, Heidi; Balloch, Anne; Chatfield, Mark; Lehmann, Deborah; Binks, Michael J; Chang, Anne; et al.
Abstract : Introduction: Streptococcus pneumoniae and non-typeable Haemophilus influenzae (NTHi) are major otitis media pathogens that densely co-colonise the nasopharynx and infect the middle ear of Australian Aboriginal infants from very early in life. Our co-primary hypotheses are that at 18 months of age infants receiving 10-valent pneumococcal Haemophilus influenzae protein D conjugate vaccine (PHiD-CV10) compared with those receiving 13-valent pneumococcal conjugate vaccine (PCV13) as a booster at 12 months of age will have higher antibody levels to Haemophilus influenzae protein D and that infants receiving PCV13 will have higher antibody levels to PCV13-only serotypes 3, 6A and 19A. Methods and analyses: Our randomised controlled trial will enrol 270 Aboriginal children at 12 months of age to a booster dose of either PHiD-CV10 or PCV13. Children who completed the three-dose primary course schedules of PHiD-CV10 at 2, 4, 6 months of age; PCV13 at 2, 4, 6 months of age; or a combination schedule of PHiD-CV10 at 1, 2, 4 months of age plus PCV13 at 6 months of age are eligible. The co-primary assessor-blinded outcomes when the infants are 18 months of age are as follows: (a) IgG geometric mean concentration (GMC) and proportion with IgG ≥100 EU/mL for protein D, and (b) IgG GMC and the proportion with IgG ≥0.35 µg/mL for pneumococcal serotypes 3, 6A and 19A. Secondary immunogenicity comparisons of six primary and booster dose schedules of 10 shared serotypes at 18 months of age, nasopharyngeal carriage, all forms of otitis media, hearing loss and developmental milestones at 18, 24, 30 and 36 months of age will be reported. Ethics and dissemination: Ethics committees of NT Department of Health, Menzies, WA Department of Health and WA Aboriginal Health approved the study. Results will be presented to communities, at conferences and published in peer-reviewed journals. Trial registration number: NCT01735084 .